Bigger, Better, Louder: The Prosperity Gospel's Impact on Contemporary Christian Worship - Bowler, Kate (Religion and American culture, 2014)
This article makes several claims about the relationship between praise and worship music and prosperity megachurches. First, it argues that the prosperity gospel has had a significant impact on contemporary worship music in America owing to its leadership in the twin rise of the megachurch and televangelism. Second, beginning in the 1990s, prosperity megachurches pioneered forms of worship music mimicking “arena rock” that capitalized on both the scale of their sanctuaries and the sophistication of their audio/visual production. The result was a progression toward music that would be a liturgy of timing, lighting, volume and performance designed for large venues. Finally, prosperity megachurches were ideally situated to benefit from this new music, both in the music industry and in their theology. Prosperity megachurches partnered with the expanding worship industry in the creation of new worship music, while the prosperity gospel theologically undergirded the affective power and performative pageantry of Christian arena rock, narrating worship music as a tool for releasing spiritual forces of prosperity. The result was a Sunday experience for the blessed that reinforced the celebration of God’s abundant blessings through music that was bigger, better, and louder.